Knowledge, Skills, and Practices of Global Service Standards Among Graduate Students at Saint Joseph Institute of Technology (SJIT) - Rodelio B. Pasion (Randwick International of Education and Linguistics Science Journal, 2024)
This study employed a descriptive research design to examine the knowledge, skills, and practices (KSP) related to global service standards among graduate students at Saint Joseph Institute of Technology (SJIT). Using convenient sampling within the "Global Trends in Service Excellence" course, data was collected through a 30-item knowledge test and a survey questionnaire assessing skills and practices. Descriptive statistics, including mean, frequency, and percentage, were utilized for analysis. Results demonstrated a strong foundation in understanding global service standards. Additionally, student respondents showed high proficiency in collaboration, creativity, critical thinking, digital literacy, and dedication to customer-focused, ethical, and sustainable practices. While adaptability remains an area for potential growth, the findings suggest that SJIT graduate students are well-positioned to succeed in the global service environment. This study offers valuable insights for educators and institutions aiming to prepare students for careers in a globalized service sector.